Ternary combinational logic gate design based on tri-valued memristors - Li, Xiao-Jing; Wang, Xiao-Yuan; Li, Pu; Iu, Herbert H. C.; Cheng, Zhi-Qun (Frontiers in Physics, 2023)
Traditional binary combinational logic circuits are generally obtained by cascading multiple basic logic gate circuits, using more components and complicated wiring. In contrast to the binary logic circuits design in this method, ternary combinational logic circuit implementation is more complicated. In this paper, a ternary circuit design method that does not require cascading basic ternary logic gates is proposed based on a tri-valued memristor, which can directly realize specific logic functions through series connection of memristors. The ternary encoder, ternary decoder, ternary comparator and ternary data selector are implemented by this method and the effectiveness of the circuits are verified by LTSpice simulations.This is a provisional file, not the final typeset article information, which can effectively improve the efficiency of information transmission and storage. Therefore, compared with binary logic, ternary logic has stronger information processing capabilities and can solve some complex and cumbersome problems in binary logic.Memristor is a nonlinear nano-component with many excellent properties such as stable resistive performance, low power consumption, and compatibility with traditional CMOS technology. In particular, the circuit realized by memristor can have both operation and storage functions, so memristor is considered to be a strong competitor to replace traditional silicon chips and continue Moore's law. Compared with traditional digital logic circuits using CMOS, memristor-based digital logic circuits can effectively reduce the area and power consumption of the circuit (